(untitled) (Lapai Journal of Economics, 2022)
Agriculture plays key roles in Nigerian economy as it serves as a source of food to people and raw materials to industries. This study examined the impact of financial sector development on agricultural output in Nigeria, using ARDL estimation technique. It employed money supply, credit to private sector and loans to agricultural sector as indicators of financial development, while using proportion of GDP to agricultural sector as a proxy for agricultural output in Nigeria. The annual data used cover the period of 1981 – 2020. It is found in the study that agricultural sector loans have negative impact on agricultural output in both short and long-run. Then, the study also found that adjusted money supply (adjusted M2) has positive impact on agricultural sector output in the long run in Nigeria. It was concluded that financial sector development has impact on agricultural productivity in Nigeria.